2005
DOI: 10.1159/000090238
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibitory Effects of Curcumin and 5-Fluorouracil on the Growth of the Human Colon Cancer Cell Line HT-29

Abstract: The synergistic effect of combination treatment with COX-2 inhibitors and chemotherapy may be another promising therapy regimen in the future treatment of colorectal cancer. Curcumin, a major yellow pigment in turmeric which is used widely allover the world, inhibits the growth of human colon cancer cell line HT-29 significantly and specifically inhibits the expression of COX-2 protein. However, the worldwide exposure of populations to curcumin raised the question of whether this agent would enhance or inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 61 publications
6
58
0
1
Order By: Relevance
“…This study establishes, for the first time, the comparable or greater growthinhibitory and apoptotic effects of liposomal curcumin with oxaliplatin, with virtually no side effects for the former, at least in animals. Interestingly, a previous study showed synergism between curcumin and 5-fluorouracil against human colon cancer cells in vitro, associated with a 6-fold reduction of cyclooxygenase-2 protein expression (23). In our study, in vitro synergism was seen between liposomal curcumin and oxaliplatin at a 4:1 ratio, but there was no substantial synergy in vivo.…”
Section: Discussionsupporting
confidence: 47%
“…This study establishes, for the first time, the comparable or greater growthinhibitory and apoptotic effects of liposomal curcumin with oxaliplatin, with virtually no side effects for the former, at least in animals. Interestingly, a previous study showed synergism between curcumin and 5-fluorouracil against human colon cancer cells in vitro, associated with a 6-fold reduction of cyclooxygenase-2 protein expression (23). In our study, in vitro synergism was seen between liposomal curcumin and oxaliplatin at a 4:1 ratio, but there was no substantial synergy in vivo.…”
Section: Discussionsupporting
confidence: 47%
“…In one study, curcumin was tested for its ability to compromise the proapoptotic activity of camptothecin, alkylating agents and anthracyclines [47] . In other studies, curcumin instead showed synergistic growth inhibition and stimulated apoptosis in some cancer cells when combined with chemotherapeutic drugs such as bortezomib and 5-fluorouracil [48] . Therefore, the combined effect of the substances likely depends on drug-drug interactions.…”
Section: Discussionmentioning
confidence: 95%
“…Other mechanisms involved in the anticancer effects of curcumin include the downregulation of Akt, cyclooxygenase-2 (COX2), prostaglandin E2 or signal transducers and activators of transcription 3 (STAT3) (Aggarwal & Shishodia, 2006), which prevents cancer cells from escaping through alternative signaling pathways. Curcumin can also potentiate the anticancer effects of cytotoxic agents such as cisplatin, 5-fluorouracil and gemcitabine (Du et al, 2006;Kunnumakkara et al, 2007;Tsai et al, 2011).…”
Section: Anticancer Effects Of Curcuminmentioning
confidence: 99%